Improving Student Learning Outcomes Through Physics Learning Media Using Macromedia Flash - Amelia, Rini; Salamah, Ummi; Abrar, M; Desnita, Desnita; Usmeldi, Usmeldi (Universitas Pendidikan Ganesha, 2021)
In the process of learning physics, teachers can still not develop ICT-based learning media using Macromedia flash software that is effective and efficient. It is necessary to analyze articles from the results of previous studies to understand the right media for learning physics. This research was conducted to know what types of research have been carried out in the development of physics learning media using Macromedia flash software and to analyze the effect size of the influence of physics learning media using Macromedia flash software in terms of student learning outcomes based on education level, type of media developed and learning materials. The type of research used is a meta-analysis study. The subjects of this research are 21 articles on the development of physics learning media using Macromedia flash software in terms of student learning outcomes that have been tested in class published in 2011-2020. The data used in this study is a quantitative analysis by calculating the effect size using statistical parameters. The result of the research is that the best effectiveness of physics learning media using Macromedia flash software in terms of student learning outcomes based on education level is in Higher Education. The best effectiveness of the media in terms of student learning outcomes based on the type of media developed is multimedia. The best effectiveness of physics learning media in student learning outcomes based on learning materials is on motion material. It can be concluded that Multimedia that uses Macromedia flash software is a medium that can help students in learning.